Fairness in hazmat routing-scheduling: a bi-objective Stackelberg game - Mohri, Seyed Sina; Asgari, Nasrin; Farahani, Reza Zanjirani; Bourlakis, Michael; Laker, Benjamin (Elsevier, 2020)
We investigate a hazmat routing-scheduling problem. To minimize the overall expected risk, various vehicles may take different routes/schedules to avoid multiple accidents on the same link. Therefore, the company envisages two issues: (1) unfairly, a vehicle departing earlier from its origin may arrive earlier at its destination than the others leaving later; (2) focusing only on the minimization of risk may increase travel time/cost incurred by the company. We suggest a bi-objective game-theoretic formulation and solve it by a modified Adaptive Large Neighborhood Search and Simulated Annealing. We test the solution on a real-life case and extract practical insights
Keywords: Multi-objective decision making; Game theory; Hazardous materials; Vehicle routing; Transportation